The effect of finite bandwidth squeezed light on entanglement creation in the Dicke model - Messikh Azeddine, Azeddine; Wahiddin, Mohamed Ridza; Pah, Chin Hee; Ficek, Zbigniew (Institute of Physics Publishing, 2004)
We analyse the relation between local two-atom and total multi-atom entanglements in the Dicke system composed of a large number of atoms. We use concurrence as a measure of entanglement between two atoms in the multi-atom system, and the spin squeezing parameter as a measure of entanglement in the whole n-atom system. In addition, the influence of the squeezing phase and bandwidth on entanglement in the steady-state Dicke system is discussed. It is shown that the introduction of a squeezed field leads to a significant enhancement of entanglement between two atoms, and the entanglement increases with increasing degree of squeezing and bandwidth of the incident squeezed field. In the presence of a coherent field the entanglement exhibits a strong dependence on the relative phase between the squeezed and coherent fields, that can jump quite rapidly from unentangled to strongly entangled values when the phase changes from zero to π. We find that the jump of the degree of entanglement is due to a flip of the spin squeezing from one quadrature component of the atomic spin to the other component when the phase changes from zero to π. We also analyse the dependence of the entanglement on the number of atoms and find that, despite the reduction in the degree of entanglement between two atoms, a large entanglement is present in the whole n-atom system and the degree of entanglement increases as the number of atoms increases.